Corneal Allografts: Factors for and against Acceptance. (3rd October 2021) - Sakowska, Justyna; Glasner, Paulina; Zieliński, Maciej; Trzonkowski, Piotr; Glasner, Leopold
Abstract : Cornea is one of the most commonly transplanted tissues worldwide. However, it is usually omitted in the field of transplantology. Transplantation of the cornea is performed to treat many ocular diseases. It restores eyesight significantly improving the quality of life. Advancements in banking of explanted corneas and progressive surgical techniques increased availability and outcomes of transplantation. Despite the vast growth in the field of transplantation laboratory testing, standards for corneal transplantation still do not include HLA typing or alloantibody detection. This standard practice is based on immune privilege dogma that accounts for high success rates of corneal transplantation. However, the increasing need for retransplantation in high-risk patients with markedly higher risk of rejection causes ophthalmology transplantation centers to reevaluate their standard algorithms. In this review we discuss immune privilege mechanisms influencing the allograft acceptance and factors disrupting the natural immunosuppressive environment of the eye. Current developments in testing and immunosuppressive treatments (including cell therapies), when applied in corneal transplantation, may give very good results, decrease the possibility of rejection, and reduce the need for retransplantation, which is fairly frequent nowadays.